الحمض النووي التنظيمي وفعاليته في تعزيز الابتكار في المؤسسة الاقتصادية دراسة حالة المؤسسة الجزائرية للاتصالات موبيليس عنابة - - سمير رويبي; عبد الرؤوف بدايرية (My University, 2022)
This study aimed to highlight the relationship between the organizational DNA, which is represented in the following components (decision-making rights, information quality, incentive system, organizational structure) and the promotion of innovation in all its forms (administrative, marketing, technological). To study the reality of this relationship with the Algerian Telecommunications Corporation "Mobilis", a simple random sample of 45 employees was selected in a group of commercial agencies affiliated to the Annaba Regional Directorate. Relying on the questionnaire as a data collection tool, as well as the adoption of the statistical program SPSS V25 for the analysis process, and we used the descriptive analytical approach to form the theoretical part of the study. The study, given that the organizational DNA is responsible for determining the identity of the institution and influencing the customs, traditions and work systems in it. The study recommends adopting the concept of organizational DNA and its components and highlighting its importance in defining the distinct identity of the organization through its impact on promoting innovation as a pivotal element for the competitiveness, sustainability and continuity of the organization. Keywords: organizational ............................................... هدفت هذه الدراسة إلى إبراز العلاقة بين الحمض النووي التنظيمي والمتمثل في المكونات التالية )حقوق اتخاذ القرار، جودة المعلومات، نظام الحوافز، الهيكل التنظيمي( وتعزيز الابتكار بأشكاله )الإداري، التسويقي، التكنولوجي(. ولدراسة واقع هذه العلاقة لدى المؤسسة الجزائرية للاتصالات "موبيليس" تم اختيار عينة عشوائية بسيطة مكونة من 45 موظف في مجموعة من الوكالا ت التجارية التابعة للمديرية الجهوية لعنابة. وبالاعتماد على الاستبيان كأداة جمع البيانات وكذا اعتماد البرنامج الإحصائي لعملية التحليل، واستخدمنا المنهج الوصفي التحليلي لتكوين الجزء النظري للدراسة، اما المنهج المستخدم في الجزء التطبيقي هو المنهج الاستقرائي، تم التوصل إلى وجود تأثير ومساهمة للحمض النووي التنظيمي في تحقيق الابتكار داخل المؤسسة محل الدراسة، باعتبار أن الحمض النووي التنظيمي مسؤول عن تحديد هوية المؤسسة ومؤثر في عادات وتقاليد وأنظمة العمل فيها. توصي الدراسة بتبني مفهوم الحمض النووي التنظيمي ومكوناته وإبراز أهميته في تحديد الهوية المتميزة للمؤسسة من خلال تأثيره في تعزيز الابتكار كعنصر محوري لتنافسية المؤسسة وديمومتها واستمراريتها